Analysis of Changes in Sediment Concentration on the Coast of Sidoarjo Regency with Landsat 8 Satellite Image Data - Andriansyah Setyawan; Siti Zainab (TEKTONIK : Jurnal Ilmu Teknik, 2024)
Total Suspended Solid (TSS) is all solids (sand, silt, and clay) or particles suspended in water and can be in the form of living (biotic) components such as phytoplankton, zooplankton, bacteria, fungi, or dead (abiotic) components such as detritus and inorganic particles. The concentration of TSS can affect the level of quality in waters and can hinder the ability to produce organic substances in these waters. The dense activity on the coast of Sidoarjo Regency results in increased turbidity of the waters, which can trigger an increase in TSS levels due to the additional supply of materials from the land. Therefore, it is necessary to calculate the analysis of changes in TSS concentration on the coast of Sidoarjo Regency which can later be used as information for better management of coastal areas. This study will compare four algorithms, namely the Syarif Budiman algorithm (2004), the Ety Parwati algorithm (2006), the Guzman & Santaella algorithm (2009), and the Hendrata Wibisana algorithm (2019). The satellite data used is Landsat 8 image recording from 2015 – 2024. From the results of this study, it can be concluded that the Ety Parwati Algorithm model has a correlation value of 0,126, which means it has a high level of relationship with in-situ data. In this study, the largest Total Suspended Solid (TSS) concentration value was obtained in 2020 with a value of 30,787 mg/L to 35,722 mg/L and the smallest in 2023 with a value of 16,008 mg/L to 22,946 mg/L. The results of this Total Suspended Solid (TSS) data processing analysis can be used as reference material in further research.